Screening of Aflatoxin Production by Aspergillus flavus Isolates from Petroleum-contaminated Soil - Mirkhan, Sawan M.; Omar, Taha J. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2023)
Fungi are eukaryotic, heterogeneous, unicellular to filamentous, spore-bearing, and chemoorganotrophic organisms which lack chlorophyll. This present study was carried out to isolate and identify fungi from petroleum-contaminated soil. Several fungal genera which included Rhizopus spp., Mucor spp., Penicillium spp., Rhizoctonia spp., Aspergillus spp., Alternaria spp., and Cladosporiumspp. were isolated using potatoes dextrose agar, Czapek-Dox Agar, and Aspergillus flavus Differentiation Agar culture media that comparable with co-amoxiclav (1g) and chloramphenicol to prevent the growth of any bacteria. The direct plate and serial dilution agar plate methods were used for the isolation of fungi. Based on results, Aspergillusand Mucor spp. were the most predominant genera and had the highest number of colonies in the soil samples. In this investigation, seven out of 27 soil samples were morphologically (macroscopically and microscopically) identified, such as A. flavus. Aflatoxigenicity of A. flavus was detected using characteristics in Aspergillus differentiation agar and colony fluorescence on exposure to ultraviolet light. Moreover, molecular approaches were used for the detection of aflatoxigenic of the A. flavus isolates. Three structural (aflD, aflO, and aflP) and one regulatory (aflR) gene of the aflatoxin gene cluster of A. flavus were targeted for amplification by the polymerase chain reaction method. The aflatoxigenic of all six A. flavus isolates was detected molecularly which contained two structural (aflD, aflP)genes out of three structural genes, while there was no specific amplification of the aflO gene in the fourth, fifth, and sixth A. flavus which issimilar to the aflR gene in the first and second A. flavus.